Residual Stress, Thermomechanics & Infrared Imaging, Hybrid Techniques and Inverse Problems, Volume 9 Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics - Bossuyt, Sven.; Schajer, Gary.; Carpinteri, Alberto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Residual Stress, Thermomechanics& Infrared Imaging, Hybrid Techniques and Inverse Problems, Volume 9 of the Proceedings of the 2015SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the ninth volume of nine from the Conference, brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on a wide range ofareas, including: Inverse Methods Inverse Methods in Plasticity Varying Length Scales Harsh Environments Opto-Acoustical Methods Hybrid Experimental Residual Stress Modelling and Advances in Measurements Thermomechanics General Material Response Infrared Imaging  .
From the Contents: Reconstruction of Spatially Varying Random Material Properties by Self-optimizing Inverse Method -- Performance Assessment of Integrated Digital Image Correlation Versus FEM Updating -- IGMU: A Geometrically Consistent Framework for Identification From Full Field Measurement.
Keywords: Mechanics, Applied; Materials -- Analysis; Engineering mathematics; Engineering -- Data processing; Engineering Mechanics; Characterization and Analytical Technique; Mathematical and Computational Engineering Applications